Analysis of Coral Reef Conditions in the Waters of Panjang Island, Central Bangka Regency - Evitulistiono, Rizki; Kurniawan; Muftiadi, M. Rizza; Alghamdi, Munirah Aziz Abdulaziz (Coastal and Marine Journal, 2023)
Coral reefs are organisms that live at the bottom of the water and take the form of sturdy limestone formations capable of withstanding the force of ocean waves. Ecologically, coral reefs serve as habitats where various animal and plant organisms seek food and shelter. This research aims to analyze the coral reef ecosystem conditions in the waters of Panjang Island and provide recommendations for sustainable management of marine biodiversity in the waters of Panjang Island, Central Bangka Regency. The Underwater Photo Transect (UPT) method involves underwater photography using a digital or regular digital camera equipped with a waterproof housing to withstand seawater exposure. The research results indicate that the percentage of live coral cover in the waters of Panjang Island ranges from 70.07% to 14.07%, categorizing it as fair to poor according to the Minister of Environment Decree No. 4 of 2001 on the Standard for Coral Reef Damage. Fourteen coral growth forms were identified in the waters of Panjang Island, belonging to 17 coral genera. Recommendations for managing marine resources on Panjang Island include sustainable tourism development. Environmentally based tourism development can serve as a solution for sustainably utilizing coral reefs and promoting improving coastal and fisheries management based on Marine Conservation Areas.